Lateral torsional buckling design imperfections for use in non‐linear FEA. Issue 1 (8th February 2018) - Snijder, H.H.; van der Aa, R.P.; Hofmeyer, H.; van Hove, B.W.E.M.
Abstract: To perform geometrically and materially non‐linear analyses including imperfections for steel beam lateral torsional buckling, the size and shape of the geometric imperfection can be taken from EN 1993‐1‐1. The shape is prescribed as an initial bow along the weak axis of the section, excluding torsion of the cross‐section. Alternatively the shape of the imperfection can be taken equal to the lateral torsional buckling mode, including torsion. Several tables and formulae exist for the determination of the size of the imperfection. In this article, different imperfection approaches are presented for finite element simulations to evaluate lateral torsional non‐linear buckling resistances and to compare these to results obtained with design rules. Based on the comparisons made, the article concludes with a proposal for design imperfections to be used in non‐linear Finite Element Analyses (FEA) for lateral torsional buckling of beams.